Measuring Innovation Performance and Competitiveness in the Hungarian Micro-regions - Miklós Lukovics (European Regional Science Association (ERSA), 2010)
Besides globalization, or rather, parallel with it, knowledge-based economy seems to represent a highly important ground-gaining force - quasi becoming a trendy buzzword - that attracts increasing attention in developed countries, although its forms vary in different regions owing to the differing situation and set of conditions of the given area and the new type of international specialization emerging as a result of global competition. All this is a fundamental factor at the level of sub-regions, since competitiveness is determined by knowledge base on the local level. The present paper aims to develop an indicator system and a complex method to measure the connection between the innovation performance and competitiveness of local units. We try to demonstrate the determining role of the innovation performance on the regional disparities measured by the competitiveness on sub-regional level with the help of multi-variable data analyzing methods based on a determined system of viewpoints, a correctly chosen theoretical models and statistical data. In the course of our work, using cluster analysis, MDS, factor analysis etc. the 174 Hungarian sub-regions will be classified according to their development phases.
Keywords: 330; innovation performance; regional competitiveness; indicator system; multivariate analysis